BRCA-deficient mouse mammary tumor organoids to study cancer-drug resistance - Duarte, Alexandra A; Gogola, Ewa; Sachs, Norman; Barazas, Marco; Annunziato, Stefano; R de Ruiter, Julian; Velds, Arno; Blatter, Sohvi; Houthuijzen, Julia M; van de Ven, Marieke; Clevers, Hans; Borst, Piet; et al. (Nature methods, 2018)
Poly(ADP-ribose) polymerase inhibition (PARPi) is a promising new therapeutic approach for the treatment of cancers that show homologous recombination deficiency (HRD). Despite the success of PARPi in targeting HRD in tumors that lack the tumor suppressor function of BRCA1 or BRCA2, drug resistance poses a major obstacle. We developed three-dimensional cancer organoids derived from genetically engineered mouse models (GEMMs) for BRCA1- and BRCA2-deficient cancers. Unlike conventional cell lines or mammospheres, organoid cultures can be efficiently derived and rapidly expanded in vitro. Orthotopically transplanted organoids give rise to mammary tumors that recapitulate the epithelial morphology and preserve the drug response of the original tumor. Notably, GEMM-tumor-derived organoids can be easily genetically modified, making them a powerful tool for genetic studies of tumor biology and drug resistance.